The Description of the Severity Level of Dental Caries in Visually Impaired Students at The Special School (SLB) Semarang - Failasufa, hayyu (Universitas Aisyah Pringsewu, 2024)
Background: Children with special needs, especially those with visual impairments, face challenges in interacting and imagining the correct way to clean and brush their teeth, thus increasing the risk of dental health issues such as cavities or tooth decay. Purpose: The purpose of this research is to understand the description of dental caries in visually impaired children at the Special School (SLB). Method: The study was conducted using a descriptive research design with a cross-sectional approach. A total of 28 students with visual impairments, attending YKTM Budi Asih and SLB Semarang, were selected as participants for this research. The research focused on describing the dental and oral health status of these students. To assess their dental health, the DMF-T index and def-t index were utilized as measurement instruments.. Results: The special needs children who were the subjects of this study had a very low DMF-T index, reaching 43.5%, while the majority of them had a def-t index in the moderate category, which was 75%. The average DMF-T index for visually impaired children in this study was 2.60, while their average def-t index was 2.87. Conclusion: The DMF-T index for visually impaired students at SLB Semarang was recorded at 2.60, categorizing it as being within the low range.